Design and implementation of an observer-based soft sensor for a heat exchanger (2011)
The objective of this work is to describe step-by-step how to implement an observer-based soft sensor in order to estimate process variables for which a hardware sensor is not available. The design and implementation procedure is illustrated by applying it to a counter-flow double-pipe heat exchanger. The approach used to design the nonlinear observer is based on a simplified mathematical model of the process. Numerical simulations and experiments were performed in a bench-scale pilot plant in order to validate the proposed scheme.